Proceedings of the 40th International Conference on Software Engineering: Software Engineering in Society 2018
DOI: 10.1145/3183428.3183436
|View full text |Cite
|
Sign up to set email alerts
|

User feedback in the app store

Abstract: App stores allow globally distributed users to submit user feedback, in the form of user reviews, about the apps they download. Previous research has found that many of these reviews contain valuable information for software evolution, such as bug reports or feature requests, and has designed approaches for automatically extracting this information. However, the diversity of the feedback submitted by users from diverse cultural backgrounds and the consequences this diversity might imply have not been studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
(60 reference statements)
3
19
0
Order By: Relevance
“…In addition, the iOS App store separates reviews by their country of origin, while the Google Play Store separates reviews by languages. Previous studies have suggested that there exist cultural differences in how users from different countries provide app reviews [9,30]. In order to protect our study from such cultural bias, we only studied US-based users' reviews.…”
Section: Threats To Validitymentioning
confidence: 99%
“…In addition, the iOS App store separates reviews by their country of origin, while the Google Play Store separates reviews by languages. Previous studies have suggested that there exist cultural differences in how users from different countries provide app reviews [9,30]. In order to protect our study from such cultural bias, we only studied US-based users' reviews.…”
Section: Threats To Validitymentioning
confidence: 99%
“…This approach permitted to explicit modeling the changes to other requirements models in response to certain term and conditions like requirements failures. Guzman et al [50] used app stores to elicit user requirements. The authors analyzed 2,560 app reviews written by users from eight countries.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the potential influence of cultural differences on user feedback, there are few studies that have investigated this topic. To our best knowledge, only one study exists that has looked at the impact of culture in reviews written in English [13]. However, this work did not examine app reviews written in different languages and only investigated certain cultural dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In our work, we focus on two cultural dimensions: Individualism and Uncertainty Avoidance. In our previous work [13] on cultural differences on app reviews, we did not investigate this point, as only countries with similar Uncertainty Avoidance scores were selected. Our current work sheds some light on this aspect by focusing on the analysis of countries with different Individualism and Uncertainty Avoidance scores.…”
Section: Introductionmentioning
confidence: 99%